Strategi Pengembangan Usaha Petani Kelapa Sawit di Desa Tabing, Kecamatan Koto Kampar Hulu - Akbar, Rahmad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research was conducted in Tabing Village, Koto Kampar Hulu District. The purpose of this study is to analyze the business development strategies of oil palm farmers in Tabing Village, Koto Kampar Hulu District. The research location was selected using a non-probability sampling method. The research method applied in this study is the SWOT analysis. The data used consists of primary and secondary data. Primary data was obtained directly from oil palm farmers through interviews to gather firsthand information. Meanwhile, secondary data was collected from agents or middlemen of oil palm fruit by distributing questionnaires. To describe the research findings, a SWOT matrix was used to analyze the internal and external factors in the farmers' business development strategy. This analysis provides an overview of the strengths, weaknesses, opportunities, and threats faced in the development strategies implemented by the farmers. The research results indicate that oil palm farming in Tabing Village, Koto Kampar Hulu District, falls within the Supportive Strategy I or Aggressive Strategy category. This aggressive strategy utilizes all available strengths to maximize existing opportunities.